Cyber Crime among Mathematical Science Students: Implications on their Academic Performance - Adegbola, Ismail; Fadara, Oludele (RADINKA JAYA UTAMA PUBLISHER, 2022)
It is a very rampant crime among students of both secondary and tertiary institutions in Nigeria. This research intends to evaluate the effect cybercrime has on the academic performance of mathematical science students of Oyo State College of Education Lanlate, Oyo State Nigeria. This research uses a case study design method through a questionnaire. Random sampling with replacement was used to select 150 respondents from NCE I-III. The data collected were analyzed using a mean score rating. The study reveals that the majority of respondents have in-depth knowledge of what cybercrime is and how it is been perpetrated. The respondent claimed to know through friends and the Internet. Also, respondents attributed the course to poverty, peer influence, and non-prosecution of the offender by the security agency. The study revealed that student who indulges in cybercrime have difficulty concentrating in class, have poor study habits and eventually drop out of school due to poor performance students who get addicted to cybercrime often get convicted; go to prison, and eventually lose their lives. The study recommends that the government should include courses to treat cybercrime in the secondary and university curricula. Also, aggressive orientation from government mass media and religious bodies should be done to expose innocent youth to the menace of cybercrime. Also, the government should improve the economic situation of the country by providing job opportunities, empowerment, and relief funds for youth to have a better life.